Perkembangan Penyebab Penyakit Busuk Lunak Pada Tanaman Buah Naga Merah (Hylocereus Polyrhizus) di Kabupaten Banyuwangi - Denis Ardwi Hantoko; Suhartiningsih Dwi Nur Cahyani (Berkala Ilmiah Pertanian, 2023)
Red dragon fruit (Hylocereus polyrhizus) is one of the most important commodities in Indonesia. The dragon fruit production center in Indonesia is located in Banyuwangi Regency with a production of 82,544 per year. Areas in Banyuwangi that produce large quantities of dragon fruit are Bangorejo, Pesanggaran, Silirangung, Purwoharjo, and Tegaldlimo. Dragon fruit is a type of plant that has a strong resistance, but there are many factors that can cause a decrease in production, one of which is OPT. Soft rot disease in dragon fruit is an example of a pest that attacks dragon fruit plants. This disease can cause physical, physiological, and chemical changes in dragon fruit plants that affect production yields. According to several sources of bacteria that cause soft rot disease is Pectobacterium. Pectobacterium will spread quickly if the surrounding conditions are supportive, such as environmental conditions, weather, temperature, and care carried out by farmers.